2013
DOI: 10.1111/jgh.12389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatment with hydrogen sulfide on methionine‐choline deficient diet‐induced non‐alcoholic steatohepatitis in rats

Abstract: Treatment with H2 S prevented NASH induced by MCD diet in rats possibly through abating oxidative stress and suppressing inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 43 publications
5
49
1
Order By: Relevance
“…Free fatty acid incubation of HepG2 cells in vitro resulted in swollen mitochondria with increased inner matrix density and loss of cristae (Jun et al, 2011). It was found that MCD-diet induced hepatic mitochondrial dysfunction marked by enhanced reactive oxygen species formation (Luo et al, 2014) and reduced activities of Complexes I and II in this study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Free fatty acid incubation of HepG2 cells in vitro resulted in swollen mitochondria with increased inner matrix density and loss of cristae (Jun et al, 2011). It was found that MCD-diet induced hepatic mitochondrial dysfunction marked by enhanced reactive oxygen species formation (Luo et al, 2014) and reduced activities of Complexes I and II in this study.…”
Section: Discussionmentioning
confidence: 85%
“…MCD-diet led to an increased production of reactive oxygen species and at the same time decreased the activity of antioxidant enzymes (Jorgacevic et al, 2013;Luo et al, 2014). Free fatty acid incubation of HepG2 cells in vitro resulted in swollen mitochondria with increased inner matrix density and loss of cristae (Jun et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…H 2 S has been shown to be protective against NAFLD (25,32). NaHS prevents nonalcoholic steatohepatitis induced by a methionine-choline-deficient diet in rats by suppressing oxidative stress and inflammation (25). Very recently, Wu et al (37) found that NaHS mitigated the fatty liver in obese mice through antioxidant potential.…”
Section: E931mentioning
confidence: 99%
“…Conversely, TG accumulating in the liver leads to NAFLD. H 2 S has been shown to be protective against NAFLD (25,32). NaHS prevents nonalcoholic steatohepatitis induced by a methionine-choline-deficient diet in rats by suppressing oxidative stress and inflammation (25).…”
Section: E931mentioning
confidence: 99%
See 1 more Smart Citation